Analysis of the Cyber Crimes' Impacts on Businesses - Belgoziyeva, Ulpan (2017)
Global networks enable businesses to operate beyond the geographical boundaries and to make their processes more efficient. However, with digitalization, there also comes threats for businesses and sometimes companies are underestimating the risks associated with cyber-attacks. As the topic is relatively new, there are not many studies that took a deep look at the impact of cyber-attacks on the businesses and analyze those impacts from different angles. The key objective of the thesis was to cover key aspects of the impacts that cyber crimes can have on businesses, taking into account the various types of cyber-attacks, no matter the size and the sector of activity in which the company operates. To achieve this, I used synthesis analysis of real cyber-attacks cases, and I have split each effect into various categories using classification analysis. Furthermore, to study deeply the consequences that cyber incidents can have on businesses, I have analyzed in depth two large corporations that have suffered such attacks, and I have interviewed 15 experts working in the field of cyber-security. This analysis helped to achieve a complete and segmented picture of the impacts that cyber incidents had on businesses and showed how significantly these could affect business.